Exact solutions of the 2+1-dimensional Camassa–Holm Kadomtsev–Petviashvili equation - Ebadi, Ghodrat; Fard, Nazila Yousefzadeh Yousefzadeh; Triki, Houria; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2012)
This paper studies the (2 + 1)-dimensional Camassa–Holm Kadomtsev–Petviashvili equation. There are a few methods that will be utilized to carry out the integration of this equation. Those are the G'/G method as well as the exponential function method. Subsequently, the ansatz method will be applied to obtain the topological soliton solution of this equation. The constraint conditions, for the existence of solitons, will also fall out of these.
Keywords: solitons; exp-function method; G'/G method